Pembentukan Karakter di Masa Pandemi Melalui Pendidikan Agama Islam - N. Fitria Nuraeni; Amirudin Amirudin; Iqbal Amar Muzaki (Jurnal al-Thullab, 2021)
This paper aims to examine the role of Islamic religious education during the pandemic in shaping the characteristics of students. Islamic Religious Education (PAI) is a very important pillar of character education. Character education will develop well if it begins with instilling the spirit of diversity in children, therefore Islamic Religious Education materials during the pandemic are supportive for character education. By providing Islamic Religious Education learning, students are taught the Al-Qur'an and Hadith as a guide or life guide for them, given aqidah learning as their religious basis, taught morals to guide human behavior, are in the bad or good category, taught fiqh as a number of legal signs at the time of worship, and introduce the history of Islam as an exemplary life. Therefore, the main purpose of learning Islamic Religious Education is to shape the personality of the students who are represented in their behavior and mindset in everyday life. In addition, one of the successes of PAI learning during the pandemic is also determined by the implementation of appropriate learning methods. Karya tulis ini hendak mengkaji peranan dari pendidikan agama islam di masa pandemi dalam membentuk karakteristik peserta didik. Pendidikan Agama Islam (PAI) ialah sebuah pilar pendidikan karakter yang sangat utama. Pendidikan karakter akan berkembang baik bila diawali dengan ditanamkannya jiwa keberagaman kepada diri anak, maka dari itu materi-materi Pendidikan Agama Islam di masa pandemi merupakan hal yang menunjang bagi pendidikan karakter. Dengan memberikan pembelajaran Pendidikan Agama Islam, siswa diajarkan Al-Qur’an dan Hadis selaku pedoman atau panduan hidup baginya, diberikan pembelajaran aqidah selaku dasar keagamaanya, diajarkan akhlak guna menjadi pedoman perilaku manusia, terdapat pada kategori yang buruk atau baik, diajarkan fiqh selaku sejumlah rambu-rambu hukum pada saat beribadah,  dan mengenalkan sejarah islam selaku sebuah keteladanan hidup. Karenanya, tujuan utama dari pembelajaran Pendidikan Agama Islam ialah untuk membentuk kepribadian dalam diri para peserta didik yang diwakili pada perilaku serta pola pikirnya pada kehidupan keseharian. Selain itu, salah satu keberhasilan pembelajaran PAI di masa pandemi ditentukan pula oleh implementasi metode pembelajaran yang tepat.